Attitude and position determination based on craters for precision landing. (August 2016) - Shao, Wei; Gao, Xizhen; Xi, Sha; Leng, Junge; Gu, Tianhao
According to the problem of autonomous optical navigation, this paper presents an easy and high-precision algorithm to estimate the attitude and position of a lander by using at least three extracted marginal elliptic curves of craters. The geometric and algebraic constraints between the marginal elliptic curves of craters and its 2D images are derived, and then the linear equations about lander's motion are established by using Kronecker product. Consequently, the laner's attitude and position relative to targeted features are uniquely acquired from the linear equations. In particular, the algorithm is easy to carry out because all computations involved in this algorithm are linear matrix operations. The extensive experiments over simulated images and parameters demonstrate the robustness, accuracy and effectiveness of our method.